Restructuring the global vaccine industry - Félix Lobo (South Centre, 2021)
The purpose of this report is to analyse the vaccines industry under the focus of Industrial Economics as an input for the design of the pertinent instruments to promote development, manufacturing and distribution of vaccines against SARS-CoV-2 in sufficient amounts to immunize all countries as soon as possible. We also need to be prepared for future emerging infectious diseases with the potential of global expansion. The report shows that the vaccines industry is - and has been for a long time - far away from the competitive market paradigm with notorious market failures. As a result, the industry is underperforming with shortages and stockouts, exit of firms from the industry, underinvestment in research and development (R&D) and manufacturing, even an "anaemic development pipeline", all signs of market failure. After a brief review of policies implemented to tackle these problems we conclude that after the COVID-19 pandemic there is a need to implement a profound overhauling of the industry and to fundamentally reformulate and extend global public policies to stimulate R&D, manufacturing, distribution and access.
Keywords: 300; Pharmaindustrie; Arzneimittel; Welt